Under the gaze : a study of the portrayal by the New Zealand print media of Pacific Island workers in the Recognised Seasonal Employer (RSE) scheme, 2007-2012 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Media Studies at Massey University, Wellington New Zealand - Enoka, Angelynne Josephine (Massey University, 2019)
Media reporting on Pacific people in New Zealand has frequently been criticised for being sensationalised, biased and narrow. Yet, there have been few broad and systematic analyses of the nature of reporting specifically concerning Pacific Island seasonal workers in New Zealand. My thesis explores how the New Zealand print media portrayed Pacific Island seasonal workers travelling under the Recognised Seasonal Employer (RSE) scheme from 2007 to 2012. That period represented the first five years of the scheme and a time when it was in the news by virtue of its novelty in New Zealand, thereby providing a rich vein of media representations to study. My research focusses on the media themes occurring in the communities where RSE workers were living, while they were living there, so as to understand the discourse circulating in their immediate community. This provides understanding of the philosophical and cultural assumptions that underpin mainstream regional media reporting in New Zealand with regards to the particular representation of Pacific RSE workers, and how this compares with representations of Pacific people as a whole. Although the goal of my thesis is to trace the nature of the portrayal of Pacific Island workers under the RSE scheme, I have contextualised this with a review of the depiction of Pacific people dating back to their arrival in the 1950s and '60s. I look at how Pacific people were racialised in the early 1970s and compare that with coverage of the influx of Pacific Island seasonal workers in 2007, exploring underlying assumptions prevalent in the 1970s that Pacific Island workers were disruptive to New Zealand, such as by taking employment from New Zealanders or posing a threat to health, law or order. A sample of 115 articles drawn from the five regional newspapers – Bay of Plenty Times, Hawkes Bay Today, Nelson Mail, Marlborough Express and The Southland Times – was chosen for media analysis. Additionally, five selected case studies extracted from the NZ Herald, a metropolitan newspaper, for each calendar year from 2007-2012, were explored and compared to the regional sample, to help identify themes about Pacific seasonal workers that were portrayed in the wider New Zealand news media but missing from the regional coverage. I analysed the articles using interpretive thematic analysis. In this method, I looked at newspaper coverage in depth to make sense of the patterns of meaning. I identified themes used by print media to portray Island workers in regions that constitute a high number of Pacific seasonal workers during the scheme’s first five years of operation in New Zealand, and mapped these over time to investigate whether there was a shift in the discourse of stories as the scheme matured. With 115 articles assessed from 2007 to 2012, concentrating on November to March in each season when most RSE workers are in New Zealand, key themes were identified. Media analysis showed the reportage had extensive positive coverage of the scheme’s policy aims in New Zealand, with government, agency officials and industry spokespeople the most frequently cited news sources. Nine key themes; Labour shortage, RSE policy, New Zealanders first, Pastoral care, Economic benefits, New Zealand unemployment, RSE cap, RSE praises and RSE issues were represented in regional coverage across regions and time periods. The overall portrayals of Pacific Island seasonal workers under the scheme represented a more positive light in comparison to what we know broadly about historical depictions of Pacific peoples in the New Zealand media. The patterns and trends in media reporting in the studied RSE regions uncovered a more affirmative portrayal overall, but also indicated that local media perceptions shifted in particular regions as time passed. The characterisation of Pacific RSE workers by the New Zealand print media in the first five years of the scheme carried fewer stigmatising discourses than in the 1970s. However, examined critically, these seeming positive discourses can be understood as positive to those promoting capitalism and seeking cheap labour, but as positioning Pacific temporary workers as dehumanised commodities in ways that may contribute to undermining their human rights and long-term best interests. These discourses and patterns are important to understand. They fill a gap that exists in the examination of how Pacific people working in temporary labour positions have been represented by the New Zealand print media. The findings provide RSE Pacific countries with insights into the issues, challenges and successes depicted by the media about their workers, as well as alerting the New Zealand public more broadly to patterns in the way the scheme has been reported to them, and to broader patterns of racialised and economic discourse. [The RSE scheme was launched in April 2007 with a cap of 5,000 workers under the then Labour Government led by Helen Clark, but the cap was lifted to 8,000 in October 2008 and was lifted again in November 2014 from 8,000 to 9,000, and then again from 9,000 to 9,500 in December 2015 and 10,500 in December 2016. It lifted again in December 2017 to 11,100 and the latest increase was in November 2018 to 12,850. The workers are mostly sourced from the Pacific Islands. They contribute substantially to New Zealand’s economy but do not accrue any rights to citizenship in New Zealand as a result of participating in the scheme.]
Keywords: Pacific Islanders; Agricultural laborers, Foreign; Seasonal labor; Press coverage; New Zealand; 470107 Media studies